Modification of plant hormone levels and signaling as a tool in plant biotechnology. - Csukasi, Fabiana; Merchante-Berg, Catharina; Valpuesta-Fernández, Victoriano (Wiley, 2009)
Plant hormones are signal molecules, present in trace quantities, that act as major regulators of plant growth and development. They are involved in a wide range of processes such as elongation, flowering, root formation and vascular differentiation. For many years, agriculturists have applied hormones to their crops to either increase the yield, or improve the quality of the commercial product. Nowadays, the knowledge of hormone biosynthesis, degradation and signaling pathways has allowed the utilization of biotechnological tools to further improve the main agricultural crops. Natural or artificial mutants, with impaired functioning of the corresponding genes, have been adopted because of their superior phenotype in specific agricultural traits. In addition, transgenic plants have been generated to regulate internal hormone levels, or their signaling pathways, resulting in some crops that have revolutionized agriculture.
Keywords: Hormonas vegetales; Biosíntesis; Biotecnología; Plant hormones; Signaling; Biosynthesis; Biotechnology